Clearing the Path to Truth: Clearing the Plains: Disease, Politics of Starvation and the Loss of Aboriginal Life, by James Daschuk, and the narrative of Canadian history. A Commentary - Kelm, Mary-Ellen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
This paper considers how Clearing the Plains helps contextualize, through Canada’s long history of settler colonialism, the findings of the Truth and Reconciliation Commission.